Quality costs of machine-building enterprises in Ukraine: a control mechanism - Olga Maslak,; Natalya Grishko,; Mariya Maslak,; Skliar, Maksym (Technium Social Sciences Journal, 2020)
This article deals with the mechanism of quality costs management of machine-building enterprises and the assessment of the impact of these costs on the economic performance of enterprises. The analysis of literature sources on the issue of quality costs analysis has helped to identify the need to determine the determinants of quality cost items for machine-building enterprises, especially within Ukraine. The authors select national machine-building enterprises for the research. The researchers analyze the impact of the cost of sales and other types of costs on the net income from the sale of products, which is the basis for the formation of the enterprise's profits. To identify the determining quality cost items, the researchers investigate the effect of the quality cost items on the cost of sales. The article deals with making mathematical models for the studied enterprises, as well as the algorithm for performing the analysis. The results of the study indicate the impact of the cost of sales on the net income from the sale of products of enterprises, which is the most significant factor among the studied ones. The results also indicate the significant impact of certain quality cost items on the cost of sales. The results of this study can be applied at the practical level in the analysis and management of quality costs of machine-building enterprises and other industries.